Foundation of the Hennies Brothers Letterpress Printing in São Paulo: A case study on a historiographical perspective - Piaia, Jade Samara [UNESP] (My University, 2024)
This article reviews historiographical methods applied to typography in Brazil, as well as more recent literature on graphic memory and microhistory as part of historiography. Intending to elucidate the history of the Hennies Brothers Letterpress Printing Shop in São Paulo this research, whose methodology cross-references different data sources and reduces the scale of observation, focused on the shop’s foundational years and the social relations through which it became part of the São Paulo letterpress printing sphere. These relations reveal, through printed materials and documents, an intense contact with immigrant communities that settled in São Paulo, distinct corporate compositions, typographers skilled in several languages, international contacts with graphic material suppliers and type foundries. The resulting narrative, which addresses the early trajectory of the Hennies Brothers—between 1891 and 1899—, was used as a case study to demonstrate methodological procedures as possibilities for revealing deeper aspects in historical research, contributing to a reflection on historiographical work in typography.
O estabelecimento da Tipografia Hennies Irmãos em São Paulo: um estudo de caso pela perspectiva historiográfica
Keywords: Design history; Graphic memory; Letterpress printing shop; Material culture; Typography